Formulation in Action. Applying Psychological Theory to Clinical Practice - Moghaddam, Nima (De Gruyter, 2015)
When people seek psychological support, formulation is the theory-driven methodology used by many practitioners to guide identification of the processes, mechanisms, and patterns of behaviour that appear to be contributing to the presenting difficulties. However, the process of formulating - or applying psychological theory to practice - can often seem unclear. In this volume, we present multiple demonstrations of formulation in action - written by applied psychologists embedded in clinical training, research, and practice. The volume covers a range of contemporary approaches to formulation and therapy that have not been considered in extant works, and includes unique sections offering critical counter-perspectives and commentaries on each approach (and its application) by authors working from alternative theoretical positions.